NOD-Like Receptor Protein 3 Inflammasome-Dependent IL-1β Accelerated ConA-Induced Hepatitis - Luan, Jingyun; Zhang, Xuyao; Wang, Shaofei; Li, Yubin; Fan, Jiajun; Chen, Wei; Zai, Wenjing; Wang, Sijia; Wang, Yichen; Chen, Mingkuan; Meng, Guangxun; Ju, Dianwen (Frontiers in Immunology, 2018)
Autoimmune hepatitis (AIH) is a progressive inflammatory disorders of unknown etiology, characterized by immune-mediated destruction of hepatocytes and massive production of cytokines. Interleukin-1β is a pleiotropic proinflammatory cytokine and well known to be critical in a variety of autoimmune diseases. However, the role of interleukin-1β (IL-1β) in AIH is still indistinct. Here, we first investigated the significance of NOD-like receptor protein 3 (NLRP3) inflammasome-dependent IL-1β in the pathogenesis of AIH with a murine model of immune-mediated hepatitis induced by Concanavalin A (ConA). In ConA-treated mice, pathogenic elevated NLRP3, Cleaved caspase-1 and IL-1β levels, as well as an inflammatory cell death known as pyroptosis predominantly occurred in the livers. Strikingly, NLRP3-/- and caspase-1-/- mice were broadly protected from hepatitis as determined by decreased histological liver injury, serum aminotransferase (ALT)/aspartate transaminase (AST) levels and pyroptosis. In vivo intervention with recombinant human interleukin-1 receptor antagonist (rhIL-1Ra) strongly suppressed ConA-induced hepatitis by decreasing tumor necrosis factor-alpha (TNF-α) and interleukin-17 (IL-17) secretion, and inflammatory cell infiltration into livers. Additionally, rhIL-1Ra-pretreated mice developed significantly reduced NLRP3 inflammasome activation and reactive oxygen species (ROS) generation. Scavenging of ROS by N-acetyl-cysteine (NAC) also attenuated NLRP3 inflammasome activation and liver inflammation, indicating that the essential role of ROS in mediating NLRP3 inflammasome activation in ConA-induced hepatitis. In conclusion, our results demonstrated that NLRP3 inflammasome-dependent IL-1β production was crucial in the pathogenesis of ConA-induced hepatitis, which shed light on the development of promising therapeutic strategies for AIH by blocking NLRP3 inflammasome and IL-1β.